2017
DOI: 10.1590/1806-93042017000300004
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution for diarrhea hospitalization in São Paulo State

Abstract: Objectives: to identify spatial pattern on hospitalization rates of children with diarrhea in the counties in São Paulo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
1
3
0
1
Order By: Relevance
“…Regarding these findings, those municipalities usually have the worst socioeconomic indicators (sewage system and safe drinking water), and, along with less access to health services, this significantly increases the risk of gastrointestinal infection and acute diarrhea. Similar data were reported in other studies, with a higher occurrence of diarrhea-related deaths in inland municipalities in the states of Maranhão, Ceará, Piauí, and Pernambuco, and in northern and central–western region states [ 2 , 6 , 37 ].…”
Section: Discussionsupporting
confidence: 90%
“…Regarding these findings, those municipalities usually have the worst socioeconomic indicators (sewage system and safe drinking water), and, along with less access to health services, this significantly increases the risk of gastrointestinal infection and acute diarrhea. Similar data were reported in other studies, with a higher occurrence of diarrhea-related deaths in inland municipalities in the states of Maranhão, Ceará, Piauí, and Pernambuco, and in northern and central–western region states [ 2 , 6 , 37 ].…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, geographical proximity between the two regions can influence the spread of infectious agents associated with diarrhea in children. This hypothesis is supported by studies that found significant spatial correlation in cases of hospitalizations for diarrhea in children in the state of São Paulo, where it was observed extensively by the clustering of cases in the Northwest region (Vaz & Nascimento, 2017). These charts can not only be useful for monitoring epidemics, but can also be used to compare patterns in different epidemic diseases and locations.…”
Section: Discussionmentioning
confidence: 64%
“…Socioeconomic status was one of the main causes of diarrheal diseases among children in China (15). A study also found that the diarrheal diseases are still a crucial public health, especially in the poorest areas (16,17). Poorly populated areas generally have poor waste disposal systems, unclean drinking water sources, and difficulty accessing health services, thereby increasing the incidence of diarrhea and gastrointestinal infections (16).…”
Section: Discussionmentioning
confidence: 99%